An investigation into whether the laser drilling capabilities of a 2kW fibre laser can be enhanced using pulse train shaping - Markcoons, D.J.W.; Voisey, K.T. (Old City Publishing, 2018)
In long, ms, pulsed melt ejected based laser drilling of metals pulse train shaping has previously improved drilling efficiency. This work investigates if pulse train shaping can be exploited in the laser drilling of 0.8-2 mm mild steel with a 1070 nm wavelength 2kW IPG 2000S fibre laser. Single pulse drilling at a range of powers is used to determine the minimum pulse length, and thereby energy input, required for through hole generation. The effect on this minimum penetration energy of using pulse trains of identical 1 ms pulses, as well as pulse trains with a progressive increase in pulse power, was investigated. Drilling efficiency was improved by both multiple 1 ms pulses and progressively increasing pulses, with the multiple pulses having a greater effect, typically increasing efficiency by 35%. Cross-sections showed not all molten material was fully ejected, indicating that further efficiency improvements are possible for the conditions considered.